Austerity, Social Program Restructuring, and the Erosion of Democracy:Examining the 2012 Employment Insurance Reforms - Porter, Ann (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2015)
The austerity period in Canada, unfolding under the Harper government since 2011, has involved not just the cutting back of social programs, but a complex process of state re-regulation and restructuring in the social policy area. In announcing the turn to austerity the government stated that the post- 2008 recession deficit was to be eliminated “without raising taxes, cutting transfers to persons, including those for seniors, children and the unemployed, or cutting transfers to other levels of government that support health care and social services, Equalization, and the gas tax transfer to municipalities.” Despite this assertion, a significant re-orientation of social policy and social programs is occurring; one which has involved cuts, which is likely to have a significant impact on the level and quality of support and services available, to further increase inequalities and which charts new roles for the federal government in these areas. La période d’austérité, débutée sous le gouvernement conservateur de Harper en 2011, n’a pas seulement impliqué la coupure des programmes d’aide sociale, mais aussi, la restructuration et la re-régulation dans le domaine de la politique sociale. Malgré les déclarations faites par les conservateurs que la récession déficitaire post-2008 sera éliminée « sans augmentation des impôts, coupure des transferts personnels, incluant ceux alloués aux personnes âgées, aux enfants, et aux personnes sans emploi, et, sans coupures des transferts des autres niveaux du gouvernement qui soutiennent la santé publique et les services sociaux, la péréquation, et les transferts des impôts sur le gaz aux municipalités », une réorientation significative de la politique sociale et des programmes sociaux a pris place. Cette réorientation inclus des coupures, qui vont fort probablement avoir un impact significatif sur la qualité du soutien et des services disponibles. Cela risque également d’augmenter les inégalités, et cela délimite des nouveaux rôles pour le gouvernement fédéral dans ces domaines. Mots-Clefs : Assurance Emploi; démocratie; programmes sociaux.